STEM Carnival brings out creative inventions among school students - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP), in collaboration with the Pahang State Department of Education, recently organized a STEM (Science, Technology, Engineering and Mathematics) and Green Technology Carnival at the former’s Astaka Hall, UMP Gambang Campus on August 7, 2019.